Lights, Camera, and Action: Vertebrate Skin Sets the Stage for Immune Cell Interaction with Arthropod-Vectored Pathogens - Chong, Shu Zhen; Evrard, Maximilien; Ng, Lai Guan (Frontiers in Immunology, 2013)
Despite increasing studies targeted at host-pathogen interactions, vector-borne diseases remain one of the largest economic health burdens worldwide. Such diseases are vectored by hematophagous arthropods that deposit pathogens into the vertebrate host’s skin during a blood meal. These pathogens spend a substantial amount of time in the skin that allows for interaction with cutaneous immune cells, suggesting a window of opportunity for development of vaccine strategies. In particular, the recent availability of intravital imaging approaches has provided further insights into immune cell behavior in living tissues. Here, we discuss how such intravital imaging studies have contributed to our knowledge of cutaneous immune cell behavior and specifically, towards pathogen and tissue trauma from the arthropod bite. We also suggest future imaging approaches that may aid in better understanding of the complex interplay between arthropod-vectored pathogens and cutaneous immunity that could lead to improved therapeutic strategies.